Pengaruh Media Lagu Isi Piringku Terhadap Pengetahuan Dan Sikap Tentang Gizi Seimbang Pada Anak Min 2 Kota Bengkulu - Haredika, Afdeo Fitra; Marleni, Wisuda Andeka; Marsofely, Reka lagora (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2022)
There is still a serious issue regarding nutrition in Indonesia. Numerous health problems arise due to alackofunderstanding of balanced nutrition, and this can af ect various age groups, including schoolchildren. Childrenwholack proper nutrition may experience obstacles in physical, mental, and intellectual growth. This researchaimstoassess the impact of using media, specifically the "Isi Piringku" song, on the knowledge and attitudes relatedtobalanced nutrition among children at MIN 2 Kota Bengkulu. This study is of the Pre-Experimental type withaOneGroup Pretest Posttest design. The study population consisted of 126 individuals, with a sample of 37 selectedusingthe simple random sampling method. The data analysis results indicate a significant improvement in both knowledgeand attitudes after the intervention, as determined by the Wilcoxon signed rank test. The obtained p-value of 0.000shows that the "Isi Piringku" song has a positive impact on enhancing understanding and attitudes towardsbalanced nutrition among children at MIN 2 Kota Bengkulu. This media can serve as a valuable referenceinproviding nutritional education to children to enhance their knowledge and attitudes regarding balanced nutrition..